(untitled) (Delta Medical College Journal, 2018)
Background: Postoperative sore throat (POST) though a minor sequel after general anaesthesia with endotracheal intubation, it can be distressing to the patient. Objective: The effectiveness of lubricating endotracheal tube with 0.05% betamethasone gel or intravenous dexamethasone in reducing the postoperative sore throat was compared. Materials and method: This was a prospective study carried out among ninety ASA I and II informed consenting patients aged 20-50 years undergoing elective surgery under general anaesthesia with endotracheal intubation. The patients were randomly divided into three groups with thirty subjects in each group. Betamethasone gel (0.05%) was applied over endotracheal tube over 15 cm mark from the tip in group I, intravenous dexamethasone was given in group II and group III was taken as control. In post-anaesthesia care unit, an anesthesiologist interviewed all patients on postoperative sore throat at 1 hour, 6 hours and 24 hours after operation. Results: At 24 hours following extubation, there was statistically significant lower incidence of post-operative sore throat (POST) in betamethasone group compared to other two groups (betamethasone group 3.33%, dexamethasone group 20% and control group 26.66%, p<0.05). When the groups were compared in pairs at 24 hours, there was statistically significant difference in the incidence of POST between betamethasone group and dexamethasone group and also betamethasone group and control group with lower incidence of POST in betamethasone group, p<0.05. It was also observed that there was no significant difference of POST between dexamethasone and control group at 1 hour, 6 hours or 24 hours, p>0.05. Conclusion: It can be concluded that the use of 0.05% betamethasone gel to lubricate widely the endotracheal tube prior to intubation effectively reduces postoperative sore throat, compared to intravenous dexamethasone administration. Delta Med Col J. Jan 2018 6(2): 73-77